The Influence of Certification Incentives and Work Motivation on the Islamic Religious Education Teachers' Performance - Heri Supratiyo (Nalar Global Foundation, 2021)
This study aims to see the effect of incentives and work motivation on the performance of religious education teachers in Islamic junior high schools in Batam City. This type of research is correlation research with a quantitative approach. The data analysis technique used simple regression analysis, multiple regression and the coefficient of determination R2. The results of the study, first, there is a significant effect of teacher certification incentives on the performance of PAI teachers in Batam City with an influence level of 0.556 with a significant value of 0.000 <0.05. The magnitude of the effect is found from the R Square value of 0.309 or 30.9%. This means that the contribution of the teacher certification incentive variable (X1) on the performance of PAI SMP teachers in Batam City (Y) is 30.9%. Second, there is a significant effect of work motivation on the performance of PAI teachers in Batam City with an influence level of 0.656 with a significant value of 0.000 <0.05. The magnitude of the effect is found from the R Square value of 0.431 or 43.1%. This means that the contribution of the teacher's work motivation variable (X2) on the performance of PAI junior high school teachers in Batam City (Y) is 43.1%. Third, there is a significant effect of teacher certification incentives (X1) and work motivation (X2) together on the performance of PAI teachers in Batam City (Y) with a significant value of 0.000 <0.05 with an R Square value of 0.527 or 52.7% . This means that the contribution of the teacher certification incentive variable (X1) and teacher work motivation (X2) on the performance of PAI teachers in Batam City (Y) is 52.7%.